Characteristics of SnO2 doped ZnO-Bi2O3 ceramics - Daneu, Nina (Kovine zlitine tehnologije, 1999)
The influence of ?$SnO_2$? additions on the sintering, microstructure development and nonlinear characteristics of ZnO based ceramics in the ZnO-?$Bi_2O_3-SnO_2$? system was studied. Introduction of ?$SnO_2$? to the ZnO-?$Bi_2O_3$? system results in the formation of the ?$Bi_2Sn_2O_7$? type pyrochlore phase and the ?$Zn_2SnO_4$? type spinel phase. For Sn/Bi 1 ratio all the ?$Bi_2O_3$? is bounded in ?$Bi_2Sn_2O_7$? pyrochlore phase and sintering is hindered. Sintering is promoted after decomposition of the pyrochlore phase into a ?$Bi_2O_3$? melt and ?$Zn_2SnO_4$? type spinel phase at temperatures above 1000°C. The addition of 0.1% of ?$SnO_2$? promotes ZnO grain growth. In compositions with larger amounts of ?$SnO_2$?, growth of ZnO grains is already inhibited by the increasing amount of ?$Zn_2SnO_4$? type spinel phase. Moderate doping with ?$SnO_2$? improved nonlinear characteristics of the basic ZnO- ?$Bi_2O_3$? binary system, while a large amount of ?$SnO_2$? resulted in its degradation.
Keywords: ceramic; keramika; cinkov oksid; bizmutov oksid; kositrov oksid; sintranje; mikrostruktura; električne lastnosti